Modeling of present and future potential distribution areas of Thymus praecox opiz. in Turkey according to the Maxent algorithm (International Journal of Biology and Chemistry, 2023)
Thymus L. genus of the Lamiaceae family, which has a cosmopolitan distribution that includes annual or perennial herbs, rarely shrubs or trees, known for their pleasant smell, has medicinal and aromatic species. Although the ethnobotanical use of individuals of the genus Thymus is quite common, its consumption is often preferred as spice and medicinal tea. In this study, Thymus praecox Opiz. forms the material of the study. In this article, potential present and future distribution areas were modeled in MaxEnt 4.1 to determine the effects of climate change on the distribution areas of T. praecox in Türkiye. In the model, 2041-2060 (~2050) and 2081-2100 (~2090) periods of SSP2 4.5 and SSP5 8.5 scenarios in CanESM5.0.3 (The Canadian Earth System Model version 5) climate change model were used, together with sample points and bioclimatic variables. According to the study outputs, it is estimated that the estimated potential suitable and very suitable distribution areas of T. praecox today are 108411.705 km2 and according to the CanESM5.0.3 model, it will experience losses in very suitable and suitable distribution areas in the future, and very suitable distribution areas cannot be found in the SSP5 8.5 scenario 2081-2100 periods.